ANALISIS PENCEMARAN LOGAM BERAT PADA SEDIMEN PERMUKAAN DI DASAR PERAIRAN LAUT PULAU PASARAN - Hamid, Abdul; Riani, Etty; Warlina, Lina (REKSABUMI, 2023)
Estuaries are areas with a high risk of contamination caused by heavy metal accumulation, namely nickel (Ni), cadmium (Cd), lead (Pb), and mercury (Hg). The contamination usually comes from anthropogenic activities, such as household chores, shipping, and industrial activities. One of the water areas located around the estuary area is the sea waters on Pasaran Island. This area is known as one of the centers for producing salted fish in Lampung Province, Indonesia. The area also catches and cultivates seafood, such as fish and shellfish. This study aims to analyze the level of pollution of heavy metals, namely Ni, Cd, Pb, and Hg in surface sediments at the seabed of Pasaran Island. The research design is a descriptive quantitative method by assessing the Geoaccumulation Index (Igeo) to analyze the contamination levels. The results showed that the surface sediments on the seabed of Pasaran Island had no indications of Ni, Cd, and Hg contamination. However, the Igeo calculation results indicated Pb contamination with levels of heavy to very heavy pollution.